2016
DOI: 10.3389/fnbeh.2015.00374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mineralocorticoid Receptor Overexpression on Anxiety and Memory after Early Life Stress in Female Mice

Abstract: Early-life stress (ELS) is a risk factor for the development of psychopathology, particularly in women. Human studies have shown that certain haplotypes of NR3C2, encoding the mineralocorticoid receptor (MR), that result in gain of function, may protect against the consequences of stress exposure, including childhood trauma. Here, we tested the hypothesis that forebrain-specific overexpression of MR in female mice would ameliorate the effects of ELS on anxiety and memory in adulthood. We found that ELS increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
(90 reference statements)
1
9
2
Order By: Relevance
“…For instance, with respect to the ability to discriminate between cue-on and cue-off episodes after fear learning, LBN conditions in early life did not lead to any deficit in performance of female mice when tested in adulthood, as opposed to the clear deficits observed in males (Arp, et al, 2016). Contextual and spatial memory formation of female mice was also not affected by LBN conditions (S Kanatsou et al, 2016), which differs from what is generally reported in males (S Kanatsou et al, 2017; Naninck, et al, 2015). However, female mice did show increased anxiety after LBN conditions in early life as observed in the open field, and somewhat reduced fear memory formation (S Kanatsou, et al, 2016).…”
Section: Sex Differences In Outcomescontrasting
confidence: 99%
See 1 more Smart Citation
“…For instance, with respect to the ability to discriminate between cue-on and cue-off episodes after fear learning, LBN conditions in early life did not lead to any deficit in performance of female mice when tested in adulthood, as opposed to the clear deficits observed in males (Arp, et al, 2016). Contextual and spatial memory formation of female mice was also not affected by LBN conditions (S Kanatsou et al, 2016), which differs from what is generally reported in males (S Kanatsou et al, 2017; Naninck, et al, 2015). However, female mice did show increased anxiety after LBN conditions in early life as observed in the open field, and somewhat reduced fear memory formation (S Kanatsou, et al, 2016).…”
Section: Sex Differences In Outcomescontrasting
confidence: 99%
“…Contextual and spatial memory formation of female mice was also not affected by LBN conditions (S Kanatsou et al, 2016), which differs from what is generally reported in males (S Kanatsou et al, 2017; Naninck, et al, 2015). However, female mice did show increased anxiety after LBN conditions in early life as observed in the open field, and somewhat reduced fear memory formation (S Kanatsou, et al, 2016). …”
Section: Sex Differences In Outcomescontrasting
confidence: 99%
“…Third, a few groups have described effects of maternal separation and limited bedding on fear conditioning in adult mice. Specifically, Wang et al ( Wang et al, 2011a , Wang et al, 2011b ) and Kanatsou et al (2016) reported that ELS reduced freezing, 24 h after combining a tone and foot shock in the same context. However, ELS did not affect acquisition, nor extinction of a fear memory in two recent studies using contextual ( Kanatsou et al, 2016 ) and cued ( Arp et al, 2016 , Zoicas and Neumann, 2016 ) fear conditioning paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Wang et al ( Wang et al, 2011a , Wang et al, 2011b ) and Kanatsou et al (2016) reported that ELS reduced freezing, 24 h after combining a tone and foot shock in the same context. However, ELS did not affect acquisition, nor extinction of a fear memory in two recent studies using contextual ( Kanatsou et al, 2016 ) and cued ( Arp et al, 2016 , Zoicas and Neumann, 2016 ) fear conditioning paradigms. The lack of ELS-induced impairment of fear memory in the current study was somewhat unexpected, but may be due to differences in methodology that tap into overlapping, but non-identical circuits ( Smith and Bulkin, 2014 ), as we induced a contextual fear association in the absence of a tone.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional KO animals confirm an important role of the HPA-axis in moderating ELS effects, showing that corticotropin releasing hormone receptor-1 (CRHr1) mediates the corticosterone response following maternal deprivation in mice[50]. Forebrain-specific deletion and overexpression of CRHr1 further specified this receptor's role in cognitive deficits and anxiety-related behavior[51].Studies focusing on the putative protective role of Mineralocorticoid Receptor (MR) overexpression are ongoing (e.g [52]…”
mentioning
confidence: 99%